APPLICATION OF DUFLOW SURFACE WATER HYDRODYNAMIC MODEL - Joleha Joleha (Jurnal Ilmu Lingkungan, 2009)
Duflow surface water hydrodynamic model aims to describe the behaviour of rivers in theirnatural conditions or state. As in all natural conditions inhomogenities and inconsistencies doprevail, thus proving difficult to integrate all sub systems making up a single system. Despitethat, Duflow within its limits generate results that can be applied in real life situations such asplanning and construction of engineering structures, decision-making, and environmentalconservation and wetlands management. The objective of this case study was to establish adesign flood recommendable for mitigation by using duflow surface hydrodynamic model.Various design flows are simulated against the different proposed structures hence, the optimalstructure is finally recommended when economical, social and environmental constraints areconsidered in the decision making process. The measure of building a green-storage is the bestand optimal structure for flood mitigation.